Impacts of synthetic androgen and estrogenic antagonist administration on growth performance, sex steroids hormones, and immune markers of male and female broilers - Mona E.M. Younis; Fatima A. Jaber; Kamlah Ali Majrashi; Hanan A. Ghoneim; Mustafa Shukry; Manal E. Shafi; Najah M. Albaqami; Mohamed E. Abd El-Hack; Mahmoud M. Abo Ghanima (Poultry Science, 2023)
The influence of synthetic androgen and estrogenic antagonists (Tamoxifen) on body characteristics and immune response of male and female broilers and the correlation between sex hormone levels were estimated in our experiment. One day old chicks were sexed, and chicks of each sex were randomly distributed on three experimental treatments; the first treatment group (TAM20) chicks were supplied with estrogenic antagonist tamoxifen citrate 20 mg/kg body weight through oral administration for four times every other day from third until ninth d; Androgen treatment chicks were injected intramuscular with veterinary androgen AD GAN@ (Boldenone Undecylenate 50 mg) 1 cm/10 kg body weight at fifth and ninth day, and the third treatment was control. Androgen treatment reported the highest feed intake with the lowest for TAM20 treatment. Concerning carcass characteristics, early androgen injection increased breast percentage significantly compared to TAM20 treatment. Androgen supplementation increased significantly comb the percentage. However, TAM20 decreased it particularly compared to control. Moreover, the percentage of comb and shanks was substantially higher for males than females. Concerning the effects of both treatments on sex hormones, androgen showed favorable effects on testosterone and estrogen compared to Tamoxifen 20 treatment. On the other hand, the administration of TAM 20 improves phagocytic activity compared to androgen administration.